Activin-mediated alterations of the fibroblast transcriptome and matrisome control the biomechanical properties of skin wounds - Mateusz S. Wietecha (Nature Portfolio, 2020)
The relationship between histopathology, gene expression, and biochemical and mechanical properties of wounds is largely unknown. Here, the authors show that activin A alters wound healing at multiple levels by promoting pro-fibrotic gene expression and matrix deposition, thereby affecting biomechanical properties of skin wounds.